The visual research of changes in the geometry of a rivet joint for material model effect for simulation riveted joints made of EN AW 5251 - Lubas, Monika (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The paper presents the results of a numerical analysis of a single-lap joint with a blind rivet and its geometrical verification by inside views from the experiment. The research aimed to determine how the results of numerical analyses (FEM) were influenced by the method of modeling the material model and how it relates to the experimental results. As part of the analyses, a discrete riveted model and material model: linear and nonlinear were constructed. The analyses took into account various load cases (500, 800, and 900 N) to better illustrate the relationship between the numerical and experimental results. A new methodology of visualizing changes in a riveted joint’s geometry was used to validate the results. The technology of making riveted joint cross-sections was developed during a static tensile test. Samples of a single lap joint with blind rivets made of aluminum sheets were subjected to a shear load. Deformations were "frozen" during the test, and sections were prepared. The microscope photos allowed for the development of a method for visualizing the deformation of the hole and rivet. The numerical results (for various loads and various material configurations) were compared with the experimental results of geometric parameters (i.e. angles between sheets or other dimensions) on the riveted joint cross-sections. The obtained results help to understand the mechanism of failure of the blind rivet under load and the complex state of loads in various stages of deformation. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)